Greenland, Hisinger Glacier at Goodenough Land, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
View from the "divide" between Kjerulf Fiord and Dickson Fiord. In the background the eastern wall of the "unknown valley" down which Hisinger Glacier flows. "C" Mountain at the extreme left. In the right center, streams from the glacier flowing into the lake whence issues the right valley stream. August 2, 1931. (Caption from Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Fiords. Geographical Review, 22(4), 548.) Scoop Mountain Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Flords. Geographical Review, 22(4), 529-561.